Paediatricians knowledge, attitudes, and practices regarding immunizations for infants in Italy - Marinelli Paolo; Di Giuseppe Gabriella; Anastasi Daniela; Angelillo Italo F (BMC, 2009)
Abstract Background The purpose of this study was to investigate whether paediatricians have appropriate knowledge, attitudes, and behaviours regarding vaccinations for infants in Italy. Methods A random sample of 500 paediatricians received a self-administered anonymous questionnaire covering demographic and professional characteristics; knowledge about the mandatory, recommended, and not indicated vaccinations for infants; attitudes about vaccinations for infants; behaviour regarding current administration or willingness to administer mandatory or recommended vaccinations for infants and immunization education programs of the parents. Results Only 42.3% paediatricians knew all recommended vaccinations for infants and this knowledge was significantly higher in females, in those who worked a higher number of hours for week, and in those who use guidelines for immunization practice. Only 10.3% had a very favourable attitude towards the utility of the recommended vaccinations for infants and this was significantly higher in those who administered recommended vaccinations for infants. A large proportion (82.7%) of paediatricians routinely informed the parents about the recommended vaccinations for infants and this appropriate behaviour was significantly higher among younger, in those with a higher number of years in practice, and in those who administered the recommended vaccinations for infants. Conclusion Training and educational interventions are needed in order to improve knowledge, attitudes, and behaviours regarding vaccinations for infants among paediatricians.